![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(1\frac{1}{2}+x=\frac{3}{2}-7\)
<=> \(\frac{3}{2}+x=\frac{-11}{2}\)
<=> \(x=-7\)
\(\frac{1}{4}+\frac{1}{3}:3x=-5\)
<=> \(\frac{1}{3}:3x=\frac{-21}{4}\)
<=> \(3x=\frac{-4}{63}\)
<=> \(x=\frac{4}{189}\)
\(\frac{4}{5}.x=\frac{8}{35}\)
<=> \(x=\frac{2}{7}\)
\(\frac{2}{3x}-\frac{1}{4}=\frac{7}{1}\)
<=> \(\frac{2}{3x}=\frac{29}{4}\)
=> \(8=87x\)
<=> \(x=\frac{8}{87}\)
\(\frac{3}{5x}+\frac{1}{2}=\frac{1}{7}\)
<=> \(\frac{3}{5x}=\frac{-5}{14}\)
<=> \(-25x=42\)
<=> \(x=\frac{-42}{25}\)
\(1-\left(5\frac{3}{8}+x-7\frac{5}{24}\right):\left(-16.\frac{2}{3}\right)=0\)
<=> \(1-\left(\frac{43}{8}+x-\frac{173}{24}\right):\frac{-32}{3}=0\)
<=> \(\frac{43}{8}+x-\frac{173}{24}=\frac{-32}{3}\)
<=> \(\frac{43}{8}+x=\frac{-83}{24}\)
<=> \(x=\frac{-53}{6}\)
học tốt
![](https://rs.olm.vn/images/avt/0.png?1311)
a) 5x=-15 <=> x=-3
b) 1-2x=37 <=> 2x=-36 <=> x=-18
c) 2x=-57 <=> x=-57/2
\(\left(6x-16\right).7^8=2.7.7^8\Leftrightarrow6x-16=14\Leftrightarrow6x=30\Leftrightarrow x=5\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) -3x+4+5x=-10-x
-3x+4+5x+10+x=0
(-3x+5x+x)+10=0
3x+10=0
3x=-10
x=\(\dfrac{-10}{3}\)
Vậy x=\(\dfrac{-10}{3}\)
b)-x+1=-3x-8
-x+1+3x+8=0
(-x+3x)+(1+8)=0
2x+9=0
2x=-9
x=\(\dfrac{-9}{2}\)
Vậy x=\(\dfrac{-9}{2}\)
c)8-(x-1)=10+(x+5)
8-x+1=10+x+5
9-x=15+x
9-x-15-x=0
(9-15)-(x+x)=0
-6-2x=0
2x=-6
x=-3
Vậy x=-3
d)100+(x+7)-(-2x+3)=8+(x+100)
100+x+7+2x-3=8+x+100
(x+2x)+(100+7-3)=(8+100)+x
3x+104=108+x
3x+104-108-x=0
(3x-x)+(104-108)=0
2x-4=0
2x=4
x=2
Vậy x=2
e, \(\left|2x+5\right|=\left|x-1\right|\)
\(\Rightarrow\left\{{}\begin{matrix}2x+5=1-x\\2x+5=x-1\end{matrix}\right.\)
\(\Rightarrow\left\{{}\begin{matrix}3x=-4\\x=-6\end{matrix}\right.\Rightarrow\left\{{}\begin{matrix}x=-\dfrac{4}{3}\\x=-6\end{matrix}\right.\)
g, \(\left|-x+4\right|=\left|-3x-8\right|\)
\(\Rightarrow\left\{{}\begin{matrix}-x+4=3x+8\\-x+4=-3x-8\end{matrix}\right.\)
\(\Rightarrow\left\{{}\begin{matrix}-4x=4\\2x=-12\end{matrix}\right.\Rightarrow\left\{{}\begin{matrix}x=-1\\x=-6\end{matrix}\right.\)
h, \(\left|x+4\right|=\left|-3-8\right|\)
\(\Rightarrow\left|x+4\right|=\left|-11\right|=11\)
\(\Rightarrow\left\{{}\begin{matrix}x+4=-11\\x+4=11\end{matrix}\right.\Rightarrow\left\{{}\begin{matrix}x=-15\\x=7\end{matrix}\right.\)
Chúc bạn học tốt!!!
![](https://rs.olm.vn/images/avt/0.png?1311)
1: Ta có: 7x+6(3-x)=27-20+73
\(\Leftrightarrow7x+18-6x=80\)
\(\Leftrightarrow x=80-18=62\)
Vậy: x=62
2: Ta có: \(6x-5\left(x-7\right)=\left(27-514\right)-486-73\)
\(\Leftrightarrow6x-5x+35=27-514-486-73\)
\(\Leftrightarrow x+35=-1046\)
\(\Leftrightarrow x=-1081\)
Vậy: x=-1081
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\left(x+2\right)-2=0\)
\(\Rightarrow x+2-2=0\)
\(\Rightarrow x=0\)
\(\left(x+3\right)+1=7\)
\(\Rightarrow x+3+1=7\)
\(\Rightarrow x+4=7\)
\(\Rightarrow x=3\)
\(\left(3x-4\right)+4=12\)
\(\Rightarrow3x-4+4=12\)
\(\Rightarrow3x=12\)
\(\Rightarrow x=4\)
\(\left(5x+4\right)-1=13\)
\(\Rightarrow5x+4-1=13\)
\(\Rightarrow5x+3=13\)
\(\Rightarrow5x=10\)
\(\Rightarrow x=2\)
\(\left(4x-8\right)-3=5\)
\(\Rightarrow4x-8-3=5\)
\(\Rightarrow4x-11=5\)
\(\Rightarrow4x=16\)
\(\Rightarrow x=4\)
\(8-\left(2x+4\right)=2\)
\(\Rightarrow8-2x-4=2\)
\(\Rightarrow4-2x=2\)
\(\Rightarrow2x=2\)
\(\Rightarrow x=1\)
\(7+\left(5x+2\right)=14\)
\(\Rightarrow7+5x+2=14\)
\(\Rightarrow9+5x=14\)
\(\Rightarrow5x=5\)
\(\Rightarrow x=1\)
\(5-\left(3x-11\right)=1\)
\(\Rightarrow5-3x+11=1\)
\(\Rightarrow16-3x=1\)
\(\Rightarrow3x=15\)
\(\Rightarrow x=5\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(2\left(x-5\right)+3\left(2-3x\right)=5x+7\)
\(\Leftrightarrow2x-10+6-9x=5x+7\)
\(\Leftrightarrow\left(2x-9x\right)+\left(6-10\right)=5x+7\)
\(\Leftrightarrow-7x-4=5x+7\)
\(\Leftrightarrow-7x-5x=4+7\)
\(\Leftrightarrow-12x=11\)
\(\Leftrightarrow x=\frac{-11}{12}\)
\(3x-5\left(x-2\right)+7=4x-12\)
\(\Leftrightarrow3x-5x-10+7=4x-12\)
\(\Leftrightarrow\left(3x-5x\right)-\left(10-7\right)=4x-12\)
\(\Leftrightarrow-2x-3=4x-12\)
\(\Leftrightarrow-2x-4x=3-12\)
\(\Leftrightarrow-6x=-15\)
\(\Leftrightarrow x=\frac{-15}{-6}=\frac{5}{2}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a: -3x+4+5x=-10-x
=>2x+4=-x-10
=>3x=-14
hay x=-14/3
b: \(-x+1=-3x-8\)
=>-x+3x=-8-1
=>2x=-9
hay x=-9/2
c: \(8-\left(x-1\right)=10+\left(x+5\right)\)
=>x+15=8-x+1
=>x+15=9-x
=>2x=-6
hay x=-3
d: \(100+\left(x+7\right)-\left(-x+3\right)=8+\left(x+100\right)\)
=>x+7+x-3=8+x
=>2x+4-x-8=0
=>x=4